Nine Absolute Dates from the Gediminas’s Hill Research - Šmigelskas, Ramūnas (Archaeologia Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English]In 2016, exploratory archaeological research was conducted in the environs of the remains of the Vilnius Upper Castle Palace, which has been also known as the Grand Ducal Palace. The purpose of the current article was to present the results of the archaeological research conducted in 2016, the analysis of which allows for a closer look at the chronology of a wooden castle building on the Gediminas Hill. This article briefly covers the previous archaeological investigations of the Gediminas Hill. Also, the prior archaeological studies related to the early inhabiting of the Hill by people are analyzed; the chronological circumstances of a wooden castle’s emergence on the Hill based on archaeological data are overviewed as well. The archaeological research of 2016 did not result in a great quantity of finds, yet the radiocarbon dating of samples was quite large in number. The present article is aiming at the publication of results of the laboratory dating of samples that was conducted in 2016 as well as at encouraging the further academic discussion on the topic of the occurrence of a wooden castle on the Gediminas Hill, based on the possibilities provided by the statistical modelling of these results.
Keywords: Grand Ducal Palace; Gediminas Hill; radiocarbon dating; modelling of radiocarbon dates